Revendiquer le droit à émigrer via l’expression du sentiment d’injustice - Simon Mastrangelo (L’Année du Maghreb)
Among the Tunisian citizens, some do not manage to consider their future in their country of origin and hope for a better life on the other side of the Mediterranean Sea, in Europe. Because of their socioeconomic profile, some of them do not have the possibility to get a visa. The only option left for them to reach Europe is undocumented migration (harga). This type of migration requires to bypass the migration policies. This could lead them to give up and stay in Tunisia but it does not happen. Instead, they keep hope and make sense of undocumented migration through an argumentation in which they claim their right to migrate. In both their discourse and the correlative audiovisual representations on Internet, one always finds the question of injustice. This article focuses on the way the feeling of injustice serves as an argument for strenghtening their claim for their right to migrate.